Closing the hysteresis loop for soil-water characteristic curve (SWCC) of sands - V Madhavan Narayanan (2019)
Soil–Water Characteristic Curve (SWCC) represents the functional relationship between water content and soil suction. The SWCC follows different paths on drying and wetting resulting in hysteresis. Drying and wetting soil-water characteristic curves (SWCCs) are obtained for three uniform sandy soils of different grain size range using a Tempe cell and flexible wall apparatus. The test data is fitted to Fredlund and Xing’s (1994) equation with initialization of fitting parameters from Chin et al. (2010) method. The coarse-grained sand has a lower air-entry-value, residual matric suction and water-entry value than that of the fine-grained sand. The drying SWCCs of the three uniform sands were of a similar shape. The effect of confining pressure on drying SWCC was briefly studied and it was found that the air-entry-value of the sand increased slightly with a reduction in initial water content. The amount of hysteresis between the drying and wetting curves for the three sands were found to be of similar order. This suggests that the uniformity of sands plays a large role in determining the amount of hysteresis between the drying and wetting SWCCs. Under positive pore-water pressure (negative matric suction), water was observed to be continuously flowing through the sand specimen when the applied suction is higher than the hydrostatic pressure at half-height of the specimen. However, when the applied suction is equivalent to the hydrostatic pressure at half-height of the specimen, the water flow was stabilized upon saturation. Therefore, it can be concluded that the hysteresis loop for SWCC for sands can be closed at hydrostatic pressure, regardless of the type of sands.